The Effect of Electronic Tickets on Violations of Article 359 of The Criminal Code - Tia Rahayu (Proceedings Series on Social Sciences & Humanities, 2023)
The development of technology is very useful to help regulate traffic smoothly and keep road users safe. The electronic ticketing system is believed to replace manual tickets to assist the Indonesian National Police in recording various traffic violations committed by the public to be more efficient. A system that allows the dissemination of information to each police officer in real time can store data on traffic violators. In addition, electronic tickets are also useful for traffic violators, they can easily pay fines through online or banks listed on the confirmation letter. This research was conducted to analyze the effect of electronic ticketing on violators of Article 359 of the Criminal Code and the factors that influence the occurrence of violations in traffic. This research uses normative methods and uses secondary legal materials. Based on the formulation of the problems listed, it is concluded that the electronic ticket on violators of article 359 of the Criminal Code provides a good response to reduce the number of traffic accidents. The factors that influence traffic violators are divided into two, namely internal and external. It would be nice if the government through police officers more often provide socialization about electronic tickets to the public so that they understand and are deterred from the violations that have been committed.